(untitled) (The Research of Medical Science Review, 2024)
Background: Failed Spinal Anesthesia (FSA) is a significant clinical concern that occurs unexpectedly, exposes patients to an unpleasant ordeal of pain, and requires the conversion of spinal anesthesia to general anesthesia. This transition increases the risks associated with airway manipulation and the inherent complications of general anesthesia. The unpredictability of FSA poses challenges for anesthetists, impacting patient safety and surgical outcomes. This study aimed to identify and analyze factors contributing to failed spinal anesthesia in different surgeries, providing insights to improve success rates and enhance perioperative care. Methods: This comparative cross-sectional study included 275 patients through a convenient sampling technique. The participants were scheduled for different surgeries under spinal anesthesia at Mardan Medical Complex, Mardan, Pakistan, from September 2024 to November 2024. The Q-square statistical test was employed to evaluate the main dependent variable (outcome of spinal anesthesia, which was measured as failed or successful). Results: The overall occurrence of failed spinal anesthesia was 3.6%. Failed spinal block was dependent mainly on the type of surgery, as the findings of this study indicated that failure events occurred in the majority of C-section cases (10.9%, n=6), followed by orthopedic surgeries (5.5%, n=3). Other major factors involved were; the urgency of the surgery, obese BMI, and patient position (as seen in most of the orthopedic cases with injections in the lateral position).Conclusion: The findings of this study revealed that multiple factors, including patient position, type of surgery, high BMI, bloody appearance and absence of free flow CSF should be considered by anesthesia providers to minimize the risk of spinal block failure.